How is a man supposed to be a man? : male childlessness--a life course disrupted - Hadley, Robin A. (Fertility, reproduction and sexuality ;, 2021)
"The global trend of declining fertility rates and an increasingly ageing population has serious implications for individuals and institutions alike. Childless men are mostly excluded from ageing, social science and reproduction scholarship and almost completely absent from most national statistics. This unique book examines the lived experiences of a hidden and disenfranchised population: men who wanted to be fathers. It explores the complex intersections that influence childlessness over the life course"--